PENGARUH PEMBELAJARAN DEEP LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of Realistic Mathematics Education-based Deep Learning on elementary school students’ mathematical critical thinking skills. This study applies a quantitative approach through a one-group pretest-posttest design. A total of 24 fifth-grade students at Pasirtalaga 1 Elementary School were involved as research participants. Data collection was carried out through a test designed to measure students’ mathematical critical thinking skills. Data analysis was carried out using descriptive statistics, normality tests, paired sample t-tests, and N-Gain calculations. The results of the analysis indicate the development of mathematical critical thinking skills with an N-Gain score of 0.73, which is classified as high. This aspect indicates that Realistic Mathematics Education-based deep learning has a positive effect on students’ mathematical critical thinking skills.